Novel unarmored dinoflagellates from the toxigenic family kareniaceae (gymnodiniales): five new species of Karlodinium and one new Takayama from the Australian sector of the Southern Ocean - de Salas, MF; Laza-Martinez, A; Hallegraeff, GM (Journal of Phycology, 2008)
Six new species of unarmored dinoflagellates in the family Kareniaceae were isolated from the Australian sector of the Southern Ocean in March 2006: Takayama tuberculata de Salas sp. nov, Karlodinium antarcticum de Salas sp. nov., Karl. ballantinum de Salas sp. nov., Karl. conicum de Salas sp. nov., Karl. corrugatum de Salas sp. nov., and Karl. decipiens de Salas et Laza-Martnez sp. nov. These new taxa were characterized using light and electron microscopy and sequencing of the LSU rDNA and are well supported based either on their morphology or molecular phylogeny. Takayama tuberculata , isolated just north of the polar front (5557S), is genetically close to T. tasmanica , but smaller, with a significantly reduced number of amphiesmal vesicles. Medium-sized Karl. antarcticum , also isolated from near the polar front, is characterized by its long ovoid cell outline and very long apical groove. The small Karl. ballantinum has a very short apical groove. The large Karl. conicum has a distinct conical epicone and spherical posterior nucleus. The small Karl. corrugatum , from just south of the polar front, has distinctive parallel striations on the epicone surface and a distinctively shaped and placed ventral pore. The large and widespread Karl. decipiens , distributed through Southern Ocean waters from the polar front to Tasmanian coastal waters, and coastal Spain, has a helicoidal chloroplast arrangement and a large central nucleus. This study represents the first description of species in the potentially ichthyotoxic family Kareniaceae recorded from the Southern Ocean.